Evaluation of Postharvest Maturity Indices of Commercial Avocado Varieties Grown at Various Elevations Along Lebanon's Coast - Salameh, Maya; Nacouzi, Diana; Lahoud, Georgette; Riachy, Imad; El Kayal, Walid (Frontiers in Plant Science, 2022)
Avocado is known to be a climacteric fruit that must be harvested during the suitable physiological maturity stage to achieve the best edible characteristics and reach the required export standards. It is very hard to visually determine the optimum maturity phases in the different avocado varieties for harvesting especially because of the limited changes in the external fruit morphology during the maturity phase and because the harvest season is extended throughout several months. Therefore, some laboratory analyses are very crucial to determine the best timing to harvest the fruit. The aim of this study is to evaluate the postharvest maturity indices over 3 harvest stages, mainly dry matter, oil content, fruit firmness, titratable acidity, total soluble solids and fruit weight in commercial avocado varieties in regard of different altitudes and agricultural practices. The varieties in this study were: Hass, Lambhass, Ettinger, Fuerte, Pinkerton, Reed and Horshim growing on different altitudes that range from 50 m to 400 m in 7 different regions in Lebanon. Statistical comparison of maturity indices under different locations by variety and harvest stage was performed using one way ANOVA as well as by principal component analysis (PCA). The results showed a high linear correlation between DM and OC over the different harvest stages. During the late harvest stage, the weight showed a negative correlation with fruit firmness and TSS. The minimum oil content % and dry matter % were recorded for Reed variety (8.2 DM% and 9.7 OC%) and the highest oil content % and dry matter % were recorded for Fuerte variety (28.5 DM% and 21.6 OC%). Data obtained during this study is used to achieve the best edible characteristics and export standards of commercial avocado varieties growing along the Lebanese coast.